Current operator volumes of invasive coronary procedures in medicare patients: Implications for future manpower needs in the catheterization laboratory1. Issue 1 (2nd May 2012) - Maroney, Justin; Khan, Saba; Powell, Wayne; Klein, Lloyd W.
Abstract Objectives We seek to assess the per‐operator volume of diagnostic catheterizations and percutaneous coronary interventions (PCI) among US cardiologists, and its implication for future manpower needs in the catheterization laboratory. Background The number of annual Medicare PCIs peaked in 2004 and has trended downward since, however the total number of catheterization laboratories nationwide has increased. It is unknown whether these trends have resulted in a dilution of per‐operator volumes, and whether the current supply of interventional cardiologists is appropriate to meet future needs. Methods We analyzed the Centers for Medicare and Medicaid Services 2008 Medicare 5% sample file, and extracted the total number of Medicare fee‐for‐service (Medicare FFS) diagnostic catheterizations and PCIs performed in 2008. We then determined per‐physician procedure volumes using National Provider Identifier numbers. Results There were 1, 198, 610 Medicare FFS diagnostic catheterizations performed by 11, 029 diagnostic cardiologists, and there were 378, 372 Medicare FFS PCIs performed by 6, 443 interventional cardiologists in 2008. The data reveal a marked difference in the 2008 distribution of diagnostic catheterizations and PCIs among operators. Just over 10% of diagnostic catheterizations were performed by operators performing 40 or fewer Medicare FFS diagnostic catheterizations, contrasted with almost 30% of PCIs performed by operators with 40 of fewer Medicare FFS PCIs. A significant majority of interventional cardiologists (61%) performed 40 or fewer Medicare FFS PCIs in 2008. Conclusions There is a high percentage of low‐volume operators performing PCI, raising questions regarding annual volume recommendations for procedural skill maintenance, and the future manpower requirements in the catheterization laboratory. © 2012 Wiley Periodicals, Inc.